TESS GALLAGHER’S THE HUG: WHAT IS IT OUT THERE? - Sugeng Purwanto (Universitas Stikubank (UNISBANK) Semarang, 2017)
Tess Gallagher (TG)—born on July 21, 1943—is a great contemporary poet who likes playing with emotion, especially women’s emotion in every conflict presented in her poem. This also applies to The Hug, a poem she wrote in 1984 which really reflects current discursive practices in the society. The main purpose of the study is to investigate how she manipulates words, contexts and imagination to create a discursive practice. In other words, the poem was analyzed employing the three register variables (field, tenor and mode) as theorized in Functional Grammar (FG). With respect to the discourse formation, Fairclough’s theoretical framework was used. The findings show that Tess Gallagher is so talented and all-out to develop the discursive practice in a well-structured poem. So totally involved in the poem were the readers that they seemed to be drowned in a wave of poetic expression. The poet’s rhetorical strategies were discussed bit by bit in FG approach to find out how field, tenor and mode were used to represent one discourse. It is recommended that great poems be analyzed employing the linguistic approach at discourse level.Key Words: discursive practice, discourse formation, field, tenor, mode